Biomimetism of Brazil nutshell (Bertholletia excelsa) - Sônego, Marília (Universidade Federal de São Carlos, 2020)
For thousands of years, nature has accumulated countless possibilities for optimized solutions to engineering problems using limited raw material, room temperature, aqueous solutions, solar energy and renewable resources. Recently, this natural accumulated knowledge has increasingly being studied and applied to solve technical problems in studies of biomimicry and bioinspiration.One from many examples are the fruit walls of nuts and drupes which are of special interest for the development of impact and puncture resistant bioinspired structures. This project aims to identify and apply the principles responsible for the excellent mechanical properties of Brazil’s nutshell (Bertholletia excelsa) to develop polymeric composites with superior toughness and mechanical resistance. Firstly, the hierarchical levels of organization of the nutshell structure were identified through chemical analysis, optical microscopy, scanning electron microscopy (SEM) and microtomography (MicroCT). Additionally, the mechanical properties of the nutshell were evaluated in tensile, compression, hardness, and fracture toughness tests, at different length-scales. Moreover, the analysis of fractured surface was carried out by optical microscopy, SEM and MicroCT, identifying the fracture and toughness mechanisms developed by Brazil’s nutshell. Finally, the principles responsible for Brazil’s nutshell mechanical performance were applied to optimize the mechanical performance of a bioinspired polymeric composite. The developed composite is composed of a 3D printed structure of polylactic acid reinforced with 30% of carbon fiber (PLA-30CF) which was impregnated with syntactic foam (epoxy resin and hollow glass microspheres). The mechanical performance of the bioinspired composite is promising. It has density of 0.96 g/cm3, flexural elastic modulus of 2.52 GPa, and impact strength of 1.8 kJ/m2. However, adjustments and improvements in the syntactic foam are still required.
Biomimetismo do ouriço da castanha do Pará (Bertholletia excelsa)
Keywords: Bioinspiração; Ouriço da castanha do Pará; Microestrutura; Propriedades mecânicas; Compósito; Bioinspiration; Brazil nutshell; Mechanical properties; Composite; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS